Perceived Ability to Practice in Disaster Management among Public Health Nurses in Aceh, Indonesia - Putra, Ardia; Petpichetchian, Wongchan; Maneewat, Khomapak (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2011)
Background: The increasing number of disaster events around the world has challenged every country to develop better disaster-management strategies. As a part of healthcare system, public health nurses (PHNs) should be involved in caring for people in disasters. Currently, there is no known study whether PHNs of Aceh, Indonesia, working with community people who are at high risk of confronting natural disasters, are able to perform their roles and functions regarding disaster management. Methods: 252 PHNs from twenty-seven public health centers in Aceh were studied during November to December 2010 to evaluate their perceived ability to practice regarding disaster management at each disaster phase: preparedness, response, and recovery phase. The perceived ability to practice was assessed by using the 30-statement, five-point Likert-scale (0-4) of Public Health Nurses’ Perceived Ability to Practice Regarding Disaster Management Questionnaire (PHNPP-DMQ). The composite scores of each phase and the total score were calculated and transformed to percentage for ease of presentation across disaster phases.Results: Overall, the PHNs’ perceived ability to practice regarding disaster management in Aceh was at a moderate level (M=74.57%, SD=13.27). The highest mean score was for the recovery phase (M=78%), and the lowest mean score was in the preparedness phase (66.15%).Conclusion: The finding of this study evokes challenges to the local government of Aceh province to further prepare PHNs to increase their ability in disaster management.Keywords: Disaster management, practice, public health nurses